Fundamentals of quantum chemistry - House, James .E. (San Diego : Elsevier/Academic Press, 2005)
"The reader needs only basic physics and calculus, but a few mathematical topics are included in sufficient detail to bring the reader up to speed with differential equations and determinants. This book is an ideal tool for self-teaching."--BOOK JACKET.
1. 2. The Quantum Mechanical Way of Doing Things -- 3. Particles in Boxes -- 4. The Hydrogen Atom -- 5. More Complex Atoms -- 6. Vibrations and the Harmonic Oscillator -- 7. Molecular Rotation and Spectroscopy -- 8. Barrier Penetration -- 9. Diatomic Molecules -- 10. Symmetry -- 11. Huckel Molecular Orbital Methods -- 12. More Complete Molecular Orbital Methods.
First ed. published as: Fundamentals of quantum mechanics. Academic Press, c1998.
Includes bibliographical references and index.
Keywords: Quantum chemistry